A Rare Case of Severe Acrodermatitis Enteropathica During Covid-19 Lockdown. - Hussain, Taimoor; Kumar, Jasvindar; Aslam, Taimur; Khan, Saad; Ishaq, Muhammad; Kumar, Daneet (Journal of Ayub Medical College Abbottabad, 2022)
Acrodermatitis Enteropathica is a rare hereditary condition characterized by perioral dermatitis, diarrhea, and alopecia. Etiology includes autosomal recessive inheritance and acquired causes such as protein malnutrition, malabsorption syndromes, premature births, parenteral nutrition, chronic illnesses, and alcoholism. We report a case of a 12-year old boy who presented with cutaneous manifestations involving the whole body, diarrhea, and sparse hairs. A low level of plasma zinc, and alkaline phosphatase level was revealed and he was started on zinc supplements. He significantly improved in a few days, and was discharged after counseling the parents about treatment compliance. This case highlights importance of early diagnosis, and the importance of treatment compliance in Acrodermatitis Enteropathica. It also stresses the need to take measures to ensure the continuity of health dissemination especially in remote areas.